(untitled) (UUM Journal of Legal Studies, 2013)
In carriage of goods by sea, usually parties involved in the transaction are composed of a seller of goods (exporter), buyer (importer), forwarding agent, ship owner, carrier and port authority. When the contract of carriage is entered, basically it involves the shipper of goods (not necessarily the seller of goods) and the ship owner. The question normally arises are as follows: Who is the right or proper person to bring action should a breach of contract occur?; If the goods damage or loss in transit, who should claim damages for the loss or damage?; What are the laws applicable in Malaysia after 1992?. All these questions become very important due to the changes of law in England in 1992, relating to the right of suit. This paper attempts to answer all the above questions based on The Civil Law Act 1956 (The Malaysian Act), The Bill of Lading Act 1855 (The English Act) and The Carriage of Goods by Sea Act 1992 (The English Act).